2019
DOI: 10.1137/18m122306x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Waves Propagate in Random Particulate Materials

Abstract: For over 70 years it has been assumed that scalar wave propagation in (ensembleaveraged) random particulate materials can be characterised by a single effective wavenumber. Here, however, we show that there exist many effective wavenumbers, each contributing to the effective transmitted wave field. Most of these contributions rapidly attenuate away from boundaries, but they make a significant contribution to the reflected and total transmitted field beyond the low-frequency regime. In some cases at least two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(71 citation statements)
references
References 65 publications
(102 reference statements)
2
64
0
Order By: Relevance
“…Retaining only the monopole term gave an explicit formula for the reflection coefficient, analogous to (4.33) with ρ 0 = ρ 1 . It may be noted that the trial fields (2.9) have a close relationship with the QCA and, in fact, the QCA as employed in [3,4] can be derived as an optimal approximation, given the radial distribution function. The present work offers possible improvement over use of the matrix as comparison, but at the expense of introducing additional polarization fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retaining only the monopole term gave an explicit formula for the reflection coefficient, analogous to (4.33) with ρ 0 = ρ 1 . It may be noted that the trial fields (2.9) have a close relationship with the QCA and, in fact, the QCA as employed in [3,4] can be derived as an optimal approximation, given the radial distribution function. The present work offers possible improvement over use of the matrix as comparison, but at the expense of introducing additional polarization fields.…”
Section: Discussionmentioning
confidence: 99%
“…(2.13) Equations (2.11) have recently been derived in [6]; they were first developed in [8]. 3 Very informally, any particular random medium is one selected at random from a set of possible media. If the set contains only a finite number of possibilities (or is discrete and countably infinite), the probability of any sample medium being characterized by the label α is p α (say), and α p α = 1.…”
Section: Summary Of Basic Theorymentioning
confidence: 99%
“…The relationship between the acoustic impedances does not only have to do with the modification of the amplitude of the incident wave: it is also related to the fraction of the incident energy that will be reflected or transmitted. Most of the acoustic properties of materials can be studied by the application of new laboratory and numerical methods as ultrasonic characterization [4], inverse characterization with basis on the acoustic impedance measurement [5], or ensemble averaged scattering [6].…”
Section: How Does Sound Insulation Occur?mentioning
confidence: 99%
“…Here we prove that there does not exist a unique effective wavenumber but instead there are an infinite number of them. Gower et al [18] first showed that there exist many effective wavenumbers, and provided a technique, the Matching Method , to efficiently calculate the effective wave field. In the present paper and [18], we show that for some parameter regimes, at least two effective wavenumbers are needed to obtain accurate results, when compared with numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Gower et al [18] first showed that there exist many effective wavenumbers, and provided a technique, the Matching Method , to efficiently calculate the effective wave field. In the present paper and [18], we show that for some parameter regimes, at least two effective wavenumbers are needed to obtain accurate results, when compared with numerical simulations. We also provide examples of how a single effective wave approximation leads to inaccurate results for both transmission and reflection for a half-space filled with particles (figure 1).…”
Section: Introductionmentioning
confidence: 99%